PEM Fuel Cell Systems - Kunusch, Cristian (2012)
Proton Exchange Membrane (PEM) fuel cells are extensively used for mobile and portable applications. This is due to their compactness, low weight, high power density, and clean, pollutant-free operation. Besides, their low temperature of operation (typically 60–80 degrees Celsius) allows fast starting times, a key feature for automotive applications, for instance. In a PEM Fuel Cell, a hydrogen-rich fuel is injected by the anode, and an oxidant (usually pure oxygen or air) is fed through the cathode. Both electrodes are separated by a solid electrolyte that allows ionic conduction and avoids electrons circulation. The output of a PEM Fuel Cell is electric energy, with water and heat as the only by-products. In this chapter, the basics of PEM fuel cells operation are reviewed, including electrochemical equations, losses, and efficiency issues. The state-of-the-art in PEM fuel cells technology is summarised, including membranes, electrodes, catalysts, line heaters, water, and heat management devices. Control-oriented models in the literature are discussed, and typical control objectives are analysed.